Borders and guns: does violent repression impact border violence? - Oztig, Lacin, I; Gurkan, Turkan A.; Yigit, Oykum E. (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2023)
Why do some authoritarian states adopt shoot-to-kill policies at their borders, while others do not when they are equally interested in reinforcing their borders? This study makes a novel contribution to the literature of state-sanctioned border violence by laying out a causal linkage between the extent of domestic repression and the authoritarian states' willingness to implement shoot-to-kill policies at their borders. Drawing upon a constructivist framework, we argue that in states where violence is routinely applied in addressing domestic political conflicts, this violent norm has implications for authoritarian states' and their border practices. We find a positive relationship between violent repression and shoot-to-kill policies, and do so by analysing 58 authoritarian states' border-reinforcement strategies between 1990 and 2017.
Keywords: authoritarian states; shoot-to-kill policies; violent repression; norms; Constructivism; INTERNATIONAL HUMAN-RIGHTS; SECURITY; DYNAMICS; REGIME; Geography; Government & Law